PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA MASTERPIECE BLITAR - Helma Avivatul Yusna (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
At Masterpiece Blitar, purchases are still up and down from year to year. The problem in this research is the fluctuation of sales in the last 5 months. Promotion and price are factors that have been tried by the company but have not been able to provide maximum contribution to consumption. The purpose of this study was to determine the effect of promotion and price on purchasing decisions at Masterpiece Blitar. The population in this study is the consumption of Masterpiece Blitar with 120 people consuming it. The data collection technique used a closed questionnaire method. The data analysis technique used is multiple linear regression, t test and f test in this study the independent variable X1 (promotion), the independent variable X2 (price) and for the assessment variable Y (purchase decision). The results of this study can be used to maintain promotions and prices on purchasing decisions for Masterpiece Blitar.